Imaginary Worlds and Efficiency Frontiers: Should We Abandon the IQWiG Health Technology Assessment Model? - Paul C Langley (University of Minnesota Libraries Publishing, 2017)
The contribution of cost-effectiveness analysis to the pricing of pharmaceuticals in Germany is at best marginal and in many, if not most cases, absent. While this may reflect a reasonable belief that cost-effectiveness analysis adds little if anything to pricing and formulary placement decisions, its marginalization reflects considerable dissatisfaction, if not frustration, with modeling efforts by the Institut für Qualität und Wirtschaftlichkeit im Gesundheitseesen (IQWiG). In part, this reflects the rejection of quality adjusted life years (QALYs) as the common outcome standard, together with the adoption of the efficiency frontier as the default framework for modeled claims. The purpose of this commentary is to consider the merits, in the German context, of an efficiency frontier framework for cost-effectiveness and pricing decisions. The commentary concludes that the efficiency frontier framework for health technology assessment, in supporting the creation of non-evaluable claims from models or simulations, fails of to meet the standards of normal science: it fails to support claims that are credible, evaluable and replicable. It should be abandoned. If cost-effectiveness modeling is to play a constructive role in pricing negotiations in Germany then manufacturers should be required to submit evaluable claims. The most effective way of ensuring this is to require manufacturers to accompany any submission for a new product with a protocol detailing how their claims, to include those for clinical outcomes, cost-effectiveness and budget impact, are to be evaluated and reported to decision makers in a meaningful time frame.   Type: Commentary